2018
DOI: 10.3389/fgene.2018.00470
|View full text |Cite
|
Sign up to set email alerts
|

eIF4E-Dependent Translational Control: A Central Mechanism for Regulation of Pain Plasticity

Abstract: Translational control of gene expression has emerged as a key mechanism in regulating different forms of long-lasting neuronal plasticity. Maladaptive plastic reorganization of peripheral and spinal nociceptive circuits underlies many chronic pain states and relies on new gene expression. Accordingly, downregulation of mRNA translation in primary afferents and spinal dorsal horn neurons inhibits tissue injury-induced sensitization of nociceptive pathways, supporting a central role for translation dysregulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 107 publications
(135 reference statements)
0
36
0
Order By: Relevance
“…Several studies suggest that AMPK activation reduces eukaryotic translation initiation factor 2 subunit α (eIF2α) phosphorylation in several cell types ( Dong et al., 2010 ; Liang et al., 2013 ; Boß et al., 2016 ). Since eIF2α regulates ternary complex availability (eIF4F complex) ( Trinh and Klann, 2013 ), it has been suggested that metformin also reduces eIF2α-dependent translation initiation ( Price and Géranton, 2009 ; Khoutorsky and Price, 2018 ; Uttam et al., 2018 ; Megat and Price, 2018 ). A recent study from our laboratory shows that metformin diminishes chronic fructose-induced tactile allodynia (a model of insulin resistance).…”
Section: Effects Of Metformin On Painmentioning
confidence: 99%
“…Several studies suggest that AMPK activation reduces eukaryotic translation initiation factor 2 subunit α (eIF2α) phosphorylation in several cell types ( Dong et al., 2010 ; Liang et al., 2013 ; Boß et al., 2016 ). Since eIF2α regulates ternary complex availability (eIF4F complex) ( Trinh and Klann, 2013 ), it has been suggested that metformin also reduces eIF2α-dependent translation initiation ( Price and Géranton, 2009 ; Khoutorsky and Price, 2018 ; Uttam et al., 2018 ; Megat and Price, 2018 ). A recent study from our laboratory shows that metformin diminishes chronic fructose-induced tactile allodynia (a model of insulin resistance).…”
Section: Effects Of Metformin On Painmentioning
confidence: 99%
“…Remarkably, our results for Torin1-and XL388-infused groups showed that the reduced Mn-enhanced signals in the cortical area, such as the IC, S1HL, M1/2, and ACC. These results demonstrate that mTOR inhibition may have an effect on activation of other brain regions as well as pain reduction through the inhibition of phosphorylation by mTOR control [13,37]. Nevertheless, there was no difference in signal enhancement ratios between experimental groups in the V1/2 region.…”
Section: How Can Mtor Inhibition Reduce Brain Activities Of Chronic Pmentioning
confidence: 64%
“…Although the roles of mTOR pathway in cancer research have been extensively studied, there has been no in-depth study on the role of mTOR signaling in pain research. Recent studies have reported that neuropathic pain is related to structural changes in the CNS after nerve injury, known as mTOR-mediated neuronal plasticity [13][14][15][16]. The activation of mTOR regulates protein synthesis and in uences a wide range of physiological and pathological states by phosphorylating downstream effectors [12,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Translation regulation plays a major role in synaptic plasticity, memory formation and related circuitry changes and occurs via multiple mechanisms [49][50][51] . Notably, dendrites contain a large amount of locally pre-positioned ribosomes and mRNA ready for rapid onset on translation occurring during LTP [52][53][54] .…”
Section: Hypothesis: Rna G4 May Play a Key Role In Neuroplasticity Thmentioning
confidence: 99%